The Eve of the French Revolution - Lowell, Edward J. (Edward Jackson), 1845-1894 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Eve of the French Revolution" by Edward J. Lowell is a historical account written in the late 19th century. The book delves into the complex socio-political landscape of France leading up to the French Revolution, exploring the events and ideas that catalyzed this major upheaval. Lowell examines various aspects of French society, including the monarchy, the clergy, and the philosophies that fueled revolutionary thoughts. The opening of the book sets the stage for examining the context and implications of the French Revolution. It introduces the era as a time marked by a conflict of ideologies, where traditional forms of government faced the rise of revolutionary democratic ideals. The text discusses the state of France under King Louis XVI, detailing the failings of the monarchy and the creeping discontent among the populace, influenced heavily by the writings of Enlightenment philosophers. Such reflections highlight the tensions between the old order and the burgeoning desire for reform that would ultimately lead to the Revolution. (This is an automatically generated summary.)
Release date is 2004-08-01
Tonya Allen, Charles Franks and the Online Distributed Proofreading Team
Keywords: France -- History -- Revolution, 1789-1799 -- Causes; France -- Social conditions -- 18th century